Determination of 10-Hydroxy-2-Decenoic Acid Content – a Marker in Several Commercial Royal Jelly Products Collected in Vietnam - Duong, Hong Anh (H. : ĐHQGHN, 2020)
The optimized capillary electrophoresis (CE) was applied to separate and detect the 10-hydroxy-2-decenoic acid (10-HAD) in royal jelly products. The method only requires that the sample solution need to be centrifuged and filtered before analyzed by the home-made capillary electrophoresis system. Firstly, 10-HDA was separated in a fused silica column with a diameter of 50 um using 20 mM Tris/Acetic buffer (pH 8.5) as a background electrolyte and a separation voltage of -17kV. Then, 10-HDA was detected by capacitively coupled contactless conductivity detection (C4D) with the migration time less than 8 minutes. Nine commercial products of royal jelly with Vietnamese and imported origin including pure royal jelly cream, lyophilized royal jelly (powder and gel) and honey with royal jelly were collected for analysis. The results of this study showed that content of 10-HDA were detected in the range of 0.5 mg/g to 23.1 mg/g. Using paired t test showed that the difference between results obtained from CE-C4D method and from HPLC method as a reference method was not statistically significant